2001
DOI: 10.1016/s0022-2828(01)90620-0
|View full text |Cite
|
Sign up to set email alerts
|

No flow ischemia inhibits insulin signaling in the heart by decreasing intracellular pH

Abstract: Abstract-Glucose-insulin-potassium solutions exert beneficial effects on the ischemic heart by reducing infarct size and mortality and improving postischemic left ventricular function. Insulin could be the critical protective component of this mixture, although the insulin response of the ischemic and postischemic myocardium has not been systematically investigated. The aim of this work was to study the insulin response during ischemia by analyzing insulin signaling. This was evaluated by measuring changes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 33 publications
3
23
0
Order By: Relevance
“…2A). In agreement with previous data obtained in perfused hearts and cardiomyocytes in suspension (2,16), no p70S6K phosphorylation could be detected in untreated cells and AMPK activation by phenformin had no effect under these basal conditions ( Fig. 2A).…”
Section: Ampk Activation Increases Insulin Signaling By Inhibiting P7supporting
confidence: 93%
See 1 more Smart Citation
“…2A). In agreement with previous data obtained in perfused hearts and cardiomyocytes in suspension (2,16), no p70S6K phosphorylation could be detected in untreated cells and AMPK activation by phenformin had no effect under these basal conditions ( Fig. 2A).…”
Section: Ampk Activation Increases Insulin Signaling By Inhibiting P7supporting
confidence: 93%
“…In addition, PKB/Akt induces the phosphorylation and activation of the mammalian target of rapamycin (mTOR)/p70S6K pathway, which, then, phosphorylates IRS-1 on serine residues leading to the inhibition of the insulin signaling (2). AMPK phosphorylates and inhibits AS160 stimulating glucose uptake independently of insulin (3).…”
Section: Ampk Activation Enhances Insulin Action On Cardiac Pkb/mentioning
confidence: 99%
“…Data on the association of acidosis and GSK-3β are scarce. However, Beauloye et al also reported that insulin (a classical inhibitor of GSK-3β) (Grimes and Jope 2001) does not decrease GSK-3β activity in an acidotic intracellular environment, suggesting that low pH might indeed result in a higher propensity for GSK-3β activation (Beauloye et al 2001). The role of GSK-3β as a potential drug target has become more and more prominent in the last years (Phukan et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…32 Thus, it is possible that the insulin effects are mediated primarily at the time of reperfusion. For example, Jonassen et al 33 reported that increased levels of insulin administered at the time of reperfusion afforded significant protection that was mediated independently of effects of glucose metabolism and was associated with activation of cell survival signaling pathways.…”
Section: Wang Et Al Cardiac Metabolism and Function After Ischemia 2069mentioning
confidence: 99%